2000
DOI: 10.1191/096032700671433928
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons in placenta

Abstract: Concentrations of chrysene, benz [a I anthracene, benzo [a I -pyrene, benzo [h lfluoranthene, indeno [1,2,3 -c,d] pyrene, dibenz [ a,h I anthracene, and benzo [g,h,i] perylene were measured in placentas from 200 women from two cities in Ukraine, Kyiv and Dniprodzerzhinsk. The participants had no special exposures and were chosen from among subjects in an ongoing study of reproductive health. All seven of the polycyclic aromatic hydrocarbons (PAHs) were found in all placentas, with the sole exception o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Resorption of the entire litter was observed in pregnant mice orally exposed to carbon black oil, which is a petroleum refinery by-product, containing several classes of hydrocarbons, including PAHs [Hansen et al 2000]. Additionally, early studies in mice demonstrated the transplacental capacity of PAHs [Bulay and Wattenberg 1971] and human studies have shown significant accumulation of PAHs in the placenta [Gladen et al 2000], umbilical cord endothelium [Hansen et al 1992], and neonatal white blood cells [Whyatt et al 2001] from babies born to mothers who smoke.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Resorption of the entire litter was observed in pregnant mice orally exposed to carbon black oil, which is a petroleum refinery by-product, containing several classes of hydrocarbons, including PAHs [Hansen et al 2000]. Additionally, early studies in mice demonstrated the transplacental capacity of PAHs [Bulay and Wattenberg 1971] and human studies have shown significant accumulation of PAHs in the placenta [Gladen et al 2000], umbilical cord endothelium [Hansen et al 1992], and neonatal white blood cells [Whyatt et al 2001] from babies born to mothers who smoke.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…More than a year after smoking cessation, PAH-DNA adducts in human blood samples are reduced by only 50% compared with levels during smoking (34). PAHs have also been shown to accumulate in the placentas of non and ex-smokers in heavily polluted areas (16). Nevertheless, there is limited information on the effects of PAH accumulation on pregnancy outcomes.…”
mentioning
confidence: 98%
“…61). Furthermore, PAHs have been shown to cross the placenta (8,14) and form hemoglobin adducts in both maternal and fetal sera (73), in addition to forming DNA adducts in both human (37) and murine (55) trophoblast cells.…”
mentioning
confidence: 99%